Implementation of Contextual Teaching and Learning Based Physics Module on Newton's Law Material to Improve Critical Thinking Skills of Class X Students - Resiana Heri Agusti (Journal of Education and Learning Research, 2023)
This research consisted of two stages, namely the first stage of developing a CTL-based Physics module using Research and Development, through the ADDIE model approach, and the second stage of experimentation at MA Al-Ihsan Boarding School Riau. The experimental stage is to see the effect of using the developed module on improving students' critical thinking skills. The assessment of students' critical thinking skills used pretest and posttest critical thinking skills questions. Data analysis used SPSS Statistics 24 Software. The results of the module development research showed that the feasibility value by experts was 0.879 in the valid category. This shows that the CTL-based modules produced in this study are considered feasible to be used in learning Newton's Law material. The results of the experimental phase research show that there is a significant effect of the use of CTL-based modules on students' critical thinking skills. In the experimental class, critical thinking before treatment was 43.35, the low category increased to 84 good categories after treatment. Whereas in the control class critical thinking before treatment 39.4 low categories increased to 74 good categories after treatment. This means that the experimental class has further increased its critical thinking compared to the control class. The conclusion of this study is that the CTL-based Physics module on Newton's Law material is valid and the use of the developed module can improve students' critical thinking.